Pengaruh Pendidikan Dan Pelatihan, Kompetensi Serta Lingkungan Kerja Terhadap Kinerja Asn Dinas Peternakan Dan Ketahanan Pangan Kabupaten Pasuruan - Suseno, Agus; Hardianto, Willy Tri; Rifai, Muhamad (Universitas Muhammadiyah Mataram, 2022)
Professionalism in public services is supported by the quality and performance of the Civil Servants who work in government agencies. The goal of this research is to know the Effect of Education and Training, Competence and Work Environment on the Performance of Civil Servants at the Department of Animal Husbandry and Food Security in Pasuruan Regency. This research using observation and survey methods by distributing questionnaires to 55 respondents. The data obtained in this research were analyzed quantitatively using IBM SPSS Statistics Version 24. Data analysis included Validity Test, Reliability Test, Classical Assumption Test, and Hypothesis Test. The results of this research stated that education and training (X1) did not affect performance, proved by the significance value (Sig.) of the X1 variable on the t-test of 0.181 > 0.05 and the t-count value of 1.355 < t-table 2.007. Competence (X2) did not affect performance, proved by the significance value (Sig.) of the competency (X2) on the t-test of 0.003 <0.05 and the t-count value of 0.675 < t-table 2.007. However, the work environment is the most dominant variable influencing performance. This is evidenced by the significance value (Sig.) of the work environment (X3) on the t-test of 0.003 <0.05 and the t-count value of 3.116 > t-table 2.007, the Standardized Coefficient Beta value of 0.414. On the other part, education and training (X1), competence (X2), and work environment (X3) simultaneously influence performance (Y). This is evidenced by the significance value (Sig.) of the three variables in the F-test of 0.010 <0.05 and the calculated F value of 4.152 > F-table 2.78.